Unlocking locally-led resilience amid conflict and climate stress: Views from community leaders in Mali on development priorities, aid distribution, and anticipatory action - Bleck, Jaimie; Carrillo, Lucia; Gottlieb, Jessica; Kosec, Katrina; Kyle, Jordan; Soumano, Moumouni (International Food Policy Research Institute, 2024)
We surveyed 2,919 community leaders across seven regions of Mali to provide insights on the prevalence and severity of shocks and crises across localities; which types of shocks and crises are most difficult from which to recover; the formal and informal ways in which local actors are involved in aid distribution systems; and the types of programming local actors view as most beneficial for promoting resilience. Despite increasing prevalence of conflict across localities, leaders predominately cited climate-related shocks as the most difficult from which to recover— especially droughts. We find that localities vary in the inclusiveness of local governance around aid distribution: while elected mayors are almost always involved, traditional leaders, women’s group and youth leaders in villages, civil servants, and civil society leaders are each involved in 40–60% of localities. We used both a budget allocation exercise and an experimental game in which we introduced the concept of anticipatory action (AA) programming—aid that is “triggered” by an early warning signal to arrive before a shock and mitigate its worst effects—to probe preferences over aid modality. We found that leaders see value in balancing investment across resilience programming (including AA) and humanitarian response, especially food aid. However, there is some important variation between village- and commune-level officials: village-level leaders are more likely to prioritize aid modalities that target households directly, like food aid and cash transfers, while commune-level leaders are more likely to prioritize risk prevention trainings. Our findings have important policy implications for promoting local resilience in Mali, including the importance of investing more in drought resilience, engaging actors at different levels of local governance who have different information and perspectives, and simultaneously investing in capacity-building around early warning system accuracy and dissemination.